Synthesis and characterization of antibacterial dental monomers and composites - Xu, Xiaoming (2012)
The objective of this study is to synthesize antibacterial methacrylate and methacrylamide monomers and formulate antibacterial fluoride-releasing dental composites. Three antibacterial methacrylate or methacrylamide monomers containing long-chain quaternary ammonium fluoride, 1,2-methacrylamido-N,N,N-trimethyldodecan-1-aminium fluoride (monomer I), N-benzyl-11-(methacryloyloxy)-N,N-dimethylundecan-1-aminium fluoride (monomer II), and methacryloxyldecylpyridinium fluoride (monomer III) have been synthesized and analyzed by nuclear magnetic resonance (NMR) and mass spectrometry (MS). The cytotoxicity test and bactericidal test against Streptococcus mutans indicate that antibacterial monomer II is superior to monomers I and III. A series of dental composites containing 0–6% of antibacterial monomer II have been formulated and tested for degree of conversion (DC), flexure strength, water sorption, solubility, and inhibition of S. mutans biofilms. An antibacterial fluoride-releasing dental composite has also been formulated and tested for flexure strength and fluoride release. The dental composite containing 3% of monomer II has a significant effect against S. mutans biofilm formation without major adverse effects on its physical and mechanical properties. The new antibacterial monomers can be used together with the fluoride-releasing monomers containing a ternary zirconiun- fluoride chelate to formulate a new antibacterial fluoride- releasing dental composite. Such a new dental composite is expected to have higher anticaries efficacy and longer service life.